Applicability of Scoring Calyculin A-Induced Premature Chromosome Condensation Objects for Dose Assessment Including for Radiotherapy Patients - Sun, Mingzhu; Moquet, Jayne; Lloyd, David; Barnard, Stephen; Anbalagan, Selvakumar; Steel, Harriet; Sommer, Aurore; Gothard, Lone; Somaiah, Navita; Ainsbury, Elizabeth (Cytogenetic and genome research, 2024)
As an extension to a previous study, a linear calibration curve covering doses from 0 to 10 Gy was constructed and evaluated in the present study using calyculin A-induced premature chromosome condensation (PCC) by scoring excess PCC objects. The main aim of this study was to assess the applicability of this PCC assay for doses below 2 Gy that are critical for triage categorization. Two separate blind tests involving a total of 6 doses were carried out; 4 out of 6 dose estimates were within the 95% confidence limits (95% CL) with the other 2 just outside. In addition, blood samples from five cancer patients undergoing external beam radiotherapy (RT) were also analyzed, and the results showed whole-body dose estimates statistically comparable to the dicentric chromosome assay (DCA) results. This is the first time that calyculin A-induced PCC was used to analyze clinical samples by scoring excess objects. Although dose estimates for the pre-RT patient samples were found to be significantly higher than the mean value for the healthy donors and were also significantly higher than those obtained using DCA, all these pre-treatment patients fell into the same category as those who may have received a low dose (<1 Gy) and do not require immediate medical care during emergency triage. Additionally, for radiological accidents with unknown exposure scenario, PCC objects and rings can be scored in parallel for the assessment of both low- and high-dose exposures. In conclusion, scoring excess objects using calyculin A-induced PCC is confirmed to be another potential biodosimetry tool in radiological emergency particularly in mass casualty scenarios, even though the data need to be interpreted with caution when cancer patients are among the casualties.